2018
DOI: 10.1158/0008-5472.can-18-1377
|View full text |Cite
|
Sign up to set email alerts
|

HORMAD1 Is a Negative Prognostic Indicator in Lung Adenocarcinoma and Specifies Resistance to Oxidative and Genotoxic Stress

Abstract: Cancer testis antigens (CTA) are expressed in testis and placenta and anomalously activated in a variety of tumors. The mechanistic contribution of CTAs to neoplastic phenotypes remains largely unknown. Using a chemigenomics approach, we find that the CTA HORMAD1 correlates with resistance to the mitochondrial complex I inhibitor piericidin A in non-small cell lung cancer (NSCLC). Resistance was due to a reductive intracellular environment that attenuated the accumulation of free radicals. In human lung adenoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 49 publications
6
67
0
Order By: Relevance
“…Nonetheless, these data are supported by the lack of significant identifications in the comparison between L and NPE, which sustain a decrease of protein oxidation in L areas compared to PL areas to levels similar to NPE regions. Consistently, similar findings have been reported about the cervical cancer vs. high-grade cervical dysplastic lesions [10] and an increased antioxidant response has been reported to account for an increased cell resistance to genotoxic and oxidative distress in a subset of Lung adenocarcinomas [61] and the hypothesis has been proposed that an adaptive selection of best fitting clones to the sharply pro-oxidant neoplastic environment takes places along with tumour progression. However, extreme caution is required in interpreting the reduced carbonylation level of a set of proteins within the context of the extensively deranged metabolisms of neoplastic cells.…”
Section: Antioxidant and Stress Response Pathways Are Under-oxidised supporting
confidence: 81%
“…Nonetheless, these data are supported by the lack of significant identifications in the comparison between L and NPE, which sustain a decrease of protein oxidation in L areas compared to PL areas to levels similar to NPE regions. Consistently, similar findings have been reported about the cervical cancer vs. high-grade cervical dysplastic lesions [10] and an increased antioxidant response has been reported to account for an increased cell resistance to genotoxic and oxidative distress in a subset of Lung adenocarcinomas [61] and the hypothesis has been proposed that an adaptive selection of best fitting clones to the sharply pro-oxidant neoplastic environment takes places along with tumour progression. However, extreme caution is required in interpreting the reduced carbonylation level of a set of proteins within the context of the extensively deranged metabolisms of neoplastic cells.…”
Section: Antioxidant and Stress Response Pathways Are Under-oxidised supporting
confidence: 81%
“…Sanada et al (2019) evaluated the miR-143-5p molecular network in LUAD using whole-genome sequencing combined with miRNA database analysis and identified 11 prognostic target genes, including RAD51. Another study showed that the abnormal expression of other genes, such as cancer testis antigen (CTA), can also promote RAD51 filament formation and simultaneously enhance the sensitivity to DNA damaging agents (Nichols et al, 2018). Dong et al (2019) revealed that RAD51 plays an important role in radiation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer/testis antigens are a group of proteins that are specifically expressed in testis but are aberrantly expressed in cancers. Later studies have confirmed that HORMAD1 is aberrantly expressed in several cancers, including gastric cancers 7 , lung cancers 8 , 9 , basal type and triple-negative breast cancers 10 14 , and ovarian cancers 15 . Aberrant HORMAD1 expression is caused by promoter hypomethylation 8 , 13 , 14 , which is believed to be unselected due to genome-wide loss of DNA methylation in many cancers 16 .…”
Section: Introductionmentioning
confidence: 92%